What this photo is an image: the photographic series “Plano de Vôo” and “Úmido” by artist Cao Guimarães - Pessanha, Lília Márcia de Sousa (Revista do Colóquio, 2021)
The purpose of this article is to analyze the photographic series “Plano de Vôo” and “Úmido” by Minas Gerais artist Cao Guimarães. As a result of a process of returning to the collection, the artist ends up proposing new visualities to us amidst the image residues. During the investigations, we seek to understand motivations that influenced the artist's methods and creative processes. At the same time, dialogues are raised with other photographer artists in the light of the same conceptual and theoretical aspect, suggesting poetic interactions between the works.
Keywords: Cao Guimarães; collecting; photographic collection